Электронный учебник по дисциплине «Основы экологии» - Березуцкая, Н. Л.; Дзюндзюк, Б. В.; Марченко, Л. И. (УАДО, 2004)
The electron text-book was designed which combines a convenient account of a theoretical stuff, laboratory practical work and testing system. The interface is convenient for dialogue of the user with the computer that is allows to spend process of education more obviously and effectively. The protocol inaccessible to the user the is frameed in which is brought: a login name, result of testing, practical definitions and also the reports on laboratory works are generated.
Keywords: электронный учебник; основы экологии